ANALISIS HUBUNGAN WATAK KEWIRAUSAHAAN DENGAN KINERJA USAHA PETERNAKAN AYAM RAS PEDAGING DI KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Rizky Prayogo Ramadhan; Burhanuddin Burhanuddin (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2017)
Broiler farm is one of businesses that have a high risk level for production and price, but it doesn’t reduce the interest of broiler farmers to commercialize broiler. This indicates that broiler farmers have the entrepreneurial characteristics that can be studied and linked to the performance of the business itself. The objectives of this research are to identify the entrepreneurial characteristics of the broiler farmers and the correlation of entrepreneurial characteristics to the business performance of broiler farm. The results showed that risk taking character was the most dominant character owned by broiler farmers in Pamijahan, Bogor. Furthermore, the ability of breeders in carrying out their businesses had a significant correlation to the effectiveness of labor in broiler poultry. Then, the leadership skills, risk taking characters, ability to make some decisions, and the ability of breeders in carrying out their businesses had a significant correlation to determination of chicken harvested.